2017
DOI: 10.1021/acs.est.7b00401
|View full text |Cite
|
Sign up to set email alerts
|

Missing Food, Missing Data? A Critical Review of Global Food Losses and Food Waste Data

Abstract: Food losses and food waste (FLW) have become a global concern in recent years and emerge as a priority in the global and national political agenda (e.g., with Target 12.3 in the new United Nations Sustainable Development Goals). A good understanding of the availability and quality of global FLW data is a prerequisite for tracking progress on reduction targets, analyzing environmental impacts, and exploring mitigation strategies for FLW. There has been a growing body of literature on FLW quantification in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
283
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 485 publications
(367 citation statements)
references
References 103 publications
(206 reference statements)
5
283
1
7
Order By: Relevance
“…In the U.S. and other developed countries, most of the attention on food loss and waste has focused on the processing, retail, and consumer levels rather than on the farm (Alexander et al, 2017;Buzby, Wells, & Hyman, 2014;Dou et al, 2016;van der Werf & Gilliland, 2017;Xue et al, 2017). Yet numerous studies indicate that significant quantities of food are discarded or diverted at the farm level, particularly in the arena of fresh produce (WRAP, 2011;Gunders, 2012;Brautigam et al, 2014 Nennich, 2016;Alexander et al 2017;WRAP, 2017).…”
Section: Farms and Food Waste: Inserting Growers' Views Into The Convmentioning
confidence: 99%
“…In the U.S. and other developed countries, most of the attention on food loss and waste has focused on the processing, retail, and consumer levels rather than on the farm (Alexander et al, 2017;Buzby, Wells, & Hyman, 2014;Dou et al, 2016;van der Werf & Gilliland, 2017;Xue et al, 2017). Yet numerous studies indicate that significant quantities of food are discarded or diverted at the farm level, particularly in the arena of fresh produce (WRAP, 2011;Gunders, 2012;Brautigam et al, 2014 Nennich, 2016;Alexander et al 2017;WRAP, 2017).…”
Section: Farms and Food Waste: Inserting Growers' Views Into The Convmentioning
confidence: 99%
“…In the process of urbanization, human diet and consumption habits have increased the burden to the GPS and the eco-environment. The high-calorie food demand system should be changed [117] and the introduction of a fine management of the food supply system, and an accompanied reduction of food waste has become an important part of the optimization of GPS resilience [8].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the dietary and consumption structures of urban-rural residents in the process of urbanization resulted in a decline of the grain demand and an increased requirement for quality [6,7]. Therefore, protecting food security should focus not only on production, but also on retail and consumption [8,9]. In conclusion, research on food security in China has stepped into a completely new field and category [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…We also encourage economists to exercise caution when adopting FLW estimates from secondary sources. In a review of over 200 publications that estimate FLW, Xue et al (2017) found that only 20% of studies relied on direct measurement of FLW from first-hand data collection; the majority of the remaining studies applied FLW estimates from previous studies, often to a new context. Further, studies that relied on secondary data could often be traced back to a handful of seminal papers that provided early FLW estimates (Xue et al 2017).…”
Section: Opportunities and Challenges In Conducting Economic Researchmentioning
confidence: 99%